A needs-based masteral degree programme in school health education for Nepal - Baidya, Prithu Charan 1940-
The primary purpose of this study was to propose a master's degree in school health education in Nepal. To achieve this purpose, three fundamentally related problems were investigated: (1) the seious health problems in the country (2) the competency needs of school health educators and (3) the topics and concepts that needs to be incorporated in the program.
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City.
Vita.
Keywords: Health education -- Nepal